Evaluation of satisfaction regarding the NeuroGame-Card educational game as a Nursing teaching strategy (Research, Society and Development, 2021)
The objective of this study was to evaluate the satisfaction of nursing students regarding the neurogame-card game that focuses on a teaching strategy of the twelve cranial nerve pairs. This is an analytical-descriptive study, with a quantitative approach, developed with a sample of 44 participants/students/players. For data collection, which occurred from October to December 2018, all students performed a game match and then the EGameFlow scale was used to assess satisfaction, together with a game profile and affinity instrument, after the approval of the Research Ethics Committee. All students (100%) they thought that games help with learning and should be used as a teaching strategy. As for the results, it was found that 86.4% of the players have affinity for games and 79.5% have affinity for team games. In relation to the EGameFlow scale, in the domain clarity of objectives, the average was 6.43 and, in the domain improvement of knowledge, the average was 6.50, with the other domains greater than or equal to 5.19. The students' profile, their affinity for individual or group games, and their affinity for a particular type of game were able to predict EGameFlow's domains; With this, they should be used as strategies for building future games. It was concluded that the general level of student satisfaction with the NeuroGame-Card game was positive as an educational strategy for teaching the physical examination of the twelve pairs of cranial nerves.